Comparison of the Overall Motion Correlation Times of Several Mammalian Serum Albumins in Dilute Solutions Determined on the Basis of Maxwell Effect and the Debye-Stokes-Einstein Equation. - Monkos, Karol (Current Topics in Biophysics, 2018)
One of the rarely used ways of determining the overall motion correlation time of proteins is method based on the Maxwell effect. This effect consists in the appearance of a stimulated birefringence in liquids or solutions and induced by the mechanical force like shear stress in a streamline flow. To determine the overall motion correlation time for protein in dilute solution is sufficient to know the molecular mass and the ratio of the principal axes of protein, and an intrinsic viscosity. The intrinsic viscosity has been measured using an Ubbelohde-type capillary microviscometer immersed in a water-bath controlled thermostatically in the range from 5°C to 45°C for six mammalian albumins. To check the influence of solution pH on the overall motion correlation time the intrinsic viscosity value of the human serum albumin in solutions at the isoelectric point and beyond of it was measured. The thus obtained correlation times were compared with the times determined on the basis of the Debye-Stokes-Einstein equation.